Does cognitive behaviour therapy for insomnia reduce clinical levels of fatigue, anxiety and depression in cancer patients? - Fleming, L; Randell, K; Harvey, C; Espie, C (John Wiley and Sons Ltd, 2014)
Objectives This secondary analysis of data from a randomised controlled trial explores associations between common symptom clusters and evaluates pre-treatment to post-treatment changes in clinical levels of these symptoms following cognitive behaviour therapy for insomnia (CBT-I). Methods Baseline data from 113 participants with insomnia were explored to establish rates of and associations between clinical levels of fatigue, anxiety and depression across the sample. Effects of CBT-I on this symptom cluster were also explored by examining changes in pre-treatment to post-treatment levels of fatigue, anxiety and depression. Results At baseline, the most common symptom presentation was insomnia+fatigue, and 30% of the sample reported at least three co-morbid symptoms. Post-CBT, the number of those experiencing clinical insomnia and clinical fatigue decreased. There were no changes in anxiety rates from baseline to post-treatment in the CBT group and modest reductions in rates of those with clinical depression. Seven individuals (9.6%) from the CBT group were completely symptom free at post-treatment compared with 0% from the treatment as usual condition. Chi-square analysis revealed a significant relationship between group allocation and changes in symptoms of insomnia and fatigue. No such relationship was found between group allocation and mood variables. Conclusions These findings confirm the high rate of symptom co-morbidities among cancer patients and highlight strong associations between sleep and fatigue. CBT-I appears to offer generalised benefit to the symptom cluster as a whole and, specifically, is effective in reducing fatigue, which exceeded clinical cut-offs prior to implementation of the intervention. This has implications for the diagnosis/management of common symptoms in cancer patients. Copyright © 2014 John Wiley and Sons, Ltd.